P132 Defining Benchmarks For Clinical Outcomes in Idiopathic Pulmonary Fibrosis. (19th November 2012) - Cohen, AH; Bradford, WZ; Glassock, KF; Weber, F
Abstract : Introduction and Oobjectives: Idiopathic pulmonary fibrosis (IPF) is a rare, fatal, progressive, fibrotic lung disorder that results in reduced lung capacity and has a considerable deleterious effect on patient function. To date, there has been no consensus on the magnitude of treatment effect that constitutes a clinically meaningful response to IPF therapy. Since IPF shares a range of biological and prognostic features with non-small cell lung cancer (NSCLC), we conducted a systematic review of clinical trials evaluating the efficacy of therapies for NSCLC to establish a benchmark for the treatment of IPF . Methods: A literature search was performed to identify all randomised clinical trials between 1994–2010 evaluating therapies for NSCLC where a statistically significant effect of treatment on progression-free survival (PFS) or objective response rate (OR) was observed. The magnitude of the treatment effect in the NSCLC trials was compared to similar endpoints in three phase III clinical trials of pirfenidone in patients with IPF . In the NCSLC trials, PFS and OR were defined by standard conventions. In the IPF trials, PFS was defined as time to death or predefined thresholds for decline in forced vital capacity (FVC) or carbon monoxide diffusing capability. In the present analysis, objective response was defined according to predefined thresholds for change in FVC and the 6-minute walk test. Data were analysed according to the Cox proportional hazards model. Results: Twelve NCSLC trials, including a total of 13, 959 patients, were identified by the search and included in the analysis. Of these studies, nine (12, 456 patients) reported a significant effect on PFS, and seven (4, 258 patients) reported a significant effect on OR. In both cases, the analysis showed that the magnitude of the response to therapy in the NSCLC trials was consistent with the pre-specified pirfenidone efficacy thresholds in the IPF trials. Conclusion: The clinical outcome parameters in therapeutic trials in NSCLC can be used to define benchmarks for assessing effect sizes in studies conducted in patients with IPF .